Our bodies, whose property? - Phillips, Anne, 1950- (Princeton University Press, 2013)
"No one wants to be treated like an object, regarded as an item of property, or put up for sale. Yet many people frame personal autonomy in terms of self-ownership, representing themselves as property owners with the right to do as they wish with their bodies. Others do not use the language of property, but are similarly insistent on the rights of free individuals to decide for themselves whether to engage in commercial transactions for sex, reproduction, or organ sales. Drawing on analyses of rape, surrogacy, and markets in human organs, Our Bodies, Whose Property? challenges notions of freedom based on ownership of our bodies and argues against the normalization of markets in bodily services and parts. Anne Phillips explores the risks associated with metaphors of property and the reasons why the commodification of the body remains problematic. What, she asks, is wrong with thinking of oneself as the owner of one's body? What is wrong with making our bodies available for rent or sale? What, if anything, is the difference between markets in sex, reproduction, or human body parts, and the other markets we commonly applaud? Phillips contends that body markets occupy the outer edges of a continuum that is, in some way, a feature of all labor markets. But she also emphasizes that we all have bodies, and considers the implications of this otherwise banal fact for equality. Bodies remind us of shared vulnerability, alerting us to the common experience of living as embodied beings in the same world. Examining the complex issue of body exceptionalism, Our Bodies, Whose Property? demonstrates that treating the body as property makes human equality harder to comprehend"--